The role of internal marketing in improving service quality: A study of service companies - Rachman Mulyandi; B Wishman S` Siregar; Elizabeth Elizabeth; Ridnawati Ridnawati; Dede M. Riski (Journal of Economics and Business Letters, 2026)
This study examines the role of internal marketing in improving service quality at service companies. The research method employed in this study is a qualitative approach using a literature review. This study highlights that internal marketing significantly increases employee satisfaction, engagement, and commitment, which ultimately has a positive impact on the quality of service provided. Effective internal marketing practices, such as good communication, training, and recognition, play a crucial role in boosting employee motivation and performance. The research findings confirm that internal marketing is a strategic investment in human resource management that can optimize organizational performance by improving service quality. By prioritizing internal marketing, companies can create a work environment conducive to innovation, collaboration, and employee well-being, thereby supporting the achievement of sustainable organizational performance.